Socioeconomic, Environmental, and Institutional Determinants of Cattle Ranching in the State of Pará, Brazilian Amazon - Santos, Wânia Mendonça dos; Santos, Marcos Antônio Souza dos; Lopes, Maria Lúcia Bahia; Martins, Cyntia Meireles; Soares, Bruno Cabral; Loureiro, João Paulo Borges de; Costa, Juliane da Silva; Martins, Geany Cleide Carvalho; Saraiva, Joyce dos Santos; Costa, Nilson Luiz; Júnior, José de Brito Lourenço (Journal of Agricultural Studies, 2022)
This study investigates how socioeconomic, environmental, and institutional variables affect the growth of cattle ranching in the state of Pará, Brazilian Amazon. Covering the period from 1995 to 2019, we used an econometric model based on the Ordinary Least Squares method. Resultingly, we found that the price of fat cattle and the supply of rural credit exert a positive effect on herd growth. The deforestation rates are directly associated with herd expansion. More precisely, the variable for the deforestation rate, lagged by two periods, significantly impacts herd increment in the present time. Furthermore, a essential step towards increasing the cattle herd was the creation of the Agricultural Defense Agency of the state of Pará. Overall, this study shows that the expansion of cattle ranching in Pará is a multivariate phenomenon determined by socioeconomic, environmental, and institutional dynamics of the regional and national economies.